Streptococcus agalactiae in adults at chiang mai university hospital: A retrospective study - Romanee Chaiwarith (2018)
Background: Infection caused by Streptococcus agalactiae, a Group B streptococcus, is an emerging disease in non-pregnant adults. This study describes the epidemiological, clinical, and microbiological characteristics of S. agalactiae infection in adult patients in northern Thailand.Methods: A retrospective study was conducted between January 1, 2006 and December 31, 2009 at Chiang Mai University Hospital among patients aged ≥15 years, whose clinical specimens obtained from normally sterile sites grew S. agalactiae.Results: One-hundred and eighty-six patients and 197 specimens were identified during the 4-year period. Among 186 patients, 82 were documented as having invasive infection; 42 patients were male (51.2%) with the mean age of 48.5 ± 19.4 years (range 17, 83). Fifty-three patients (64.6%) had underlying medical conditions; 17 patients (20.7%), 10 (12.2%), 8 (9.7%) had diabetes, chronic renal diseases, and malignancy, respectively. Among 40 patients (48.8%) with bloodstream infection, no other site of infection was determined in 29 (35.4%) patients. In the remaining 11 patients, 5 patients (6.1%), 5 (6.1%), and 1 (1.2%) had meningitis, arthritis, and meningitis with arthritis, respectively. Forty-two patients (51.2%) presented with localized infection, i.e., subcutaneous abscess (19 patients, 23.2%), chorioamnionitis (10 patients, 12.2%), urinary tract infection (5 patients, 6.1%), arthritis (3 patients, 3.7%), meningitis (2 patients, 2.4%), and spontaneous bacterial peritonitis, uveitis, and tracheobronchitis (1 patient each, 1.2%). The overall mortality was 14.6% (12 patients).Conclusions: S. agalactiae infection is a growing problem in non-pregnant patients, particularly in those with underlying medical conditions. Physicians should add S. agalactiae infection in the list of differential diagnoses in patients with meningitis and/or septicemia. © 2011 Chaiwarith et al; licensee BioMed Central Ltd.